1990
DOI: 10.1128/mcb.10.6.2591
|View full text |Cite
|
Sign up to set email alerts
|

Transformation by v-myb correlates with trans-activation of gene expression.

Abstract: The v-myb oncogene of avian myeloblastosis virus causes acute myelomonocytic leukemia in chickens and transforms avian myeloid cells in vitro. Its protein product p48v-myb is a nuclear, sequence-specific, DNA-binding The v-myb oncogene of the avian myeloblastosis virus (AMV) causes acute myelomonocytic leukemia in chickens and transforms avian myeloid cells but not fibroblasts in vitro (for a review, see reference 29). The related E26 avian leukemia virus causes acute erythroid leukemia in chickens and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 50 publications
3
64
0
Order By: Relevance
“…In studies performed to examine the correlation between transactivation and transformation by v-Myb, Lane et al (1990) in fact generated one insertion mutant interfering with the SIM element as defined in this work (v-Myb 752; I 202 NII-I 202 NGPII). Interestingly, this mutant was able to activate transcription 25-fold more efficiently than AMV v-Myb in QT6 cells (Chen and Lipsick, 1993), suggesting that this might be due to loss of interaction with a unknown cellular inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies performed to examine the correlation between transactivation and transformation by v-Myb, Lane et al (1990) in fact generated one insertion mutant interfering with the SIM element as defined in this work (v-Myb 752; I 202 NII-I 202 NGPII). Interestingly, this mutant was able to activate transcription 25-fold more efficiently than AMV v-Myb in QT6 cells (Chen and Lipsick, 1993), suggesting that this might be due to loss of interaction with a unknown cellular inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, deregulation of c-Myb expression is associated with oncogenicity. Moreover, the transcriptional regulatory activity of Myb is crucial for its transforming ability (Gonda et al, 1989;Lane et al, 1990;Hu et al, 1991). Multiple co-factors like p300/CBP, Mi-2a, FLASH and menin/MLL engage in the regulation of the transactivational activity of c-Myb (Dai et al, 1996;Oelgeschlager et al, 1996;Kasper et al, 2002;Saether et al, 2007;Alm-Kristiansen et al, 2008;Jin et al, 2010).…”
mentioning
confidence: 99%
“…When expressing several di erent Myb derivatives (c-Myb, vMyb, a c-Myb/VP16 fusion and a v-Myb/VP16 fusion) a repression of the basal activity by an averge of 60% was observed even for those Myb proteins fused to a strong VP16 activation domain. This observed repression appears to require DNA binding by the di erent Myb proteins which were co-expressed in these transfection experiments, because no repression was observed after coexpression of a v-Myb protein which is de®cient in its DNA binding activity (v-Myb364, contains a linker insertion mutation within the DNA binding domain which abolishes DNA binding) (Lane et al, 1990). Trans-activation studies with the pGLNrasDUM reporter construct further supported that the observed repression with the pGLNras and pGLNrasDU constructs is mostly due to binding of the Myb proteins to the Myb sites, since deletion of all of the three sites resulted in derepression of the N-ras promoter.…”
Section: Repression Of the N-ras Promoter By Myb Proteins In Transienmentioning
confidence: 97%
“…The correlation between transactivation and transformation by Myb (Lane et al, 1990;Kanei-Ishii et al, 1992;Hu et al, 1991) suggests that the ability of Myb to transform hemopoietic cells is dependent on the transactivation of genes critical for this process. We have investigated the regulation of several putative Myb regulated genes in the ERMYB transformed cells and have found that cdc2 and c-myc mRNA levels do not correlate with activation of Myb.…”
Section: Apoptosis In Ermyb Cellsmentioning
confidence: 99%